Positive pole piece of large soft package battery cell, preparation method of positive pole piece, large soft package battery cell and plant protection unmanned aerial vehicle

By introducing a lithium iron manganese phosphate layer and ion transport enhancing materials into the positive electrode of the large soft-pack battery cell, a composite structure is formed, which solves the problem of insufficient puncture resistance and achieves improvements in safety and ion transport performance.

CN120637383APending Publication Date: 2025-09-12EVE ENERGY CO LTD

Patent Information

Application Number
CN202510780202.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The positive electrode plates of existing large soft-pack batteries have poor puncture resistance, resulting in insufficient safety and the risk of thermal runaway.

Method used

A lithium iron manganese phosphate layer is introduced into the positive electrode sheet as a physical barrier and ion transport enhancement material to form a stacked composite structure, blocking the thermal decomposition diffusion path, improving the ion transmission capacity, and enhancing mechanical protection.

Benefits of technology

It improves the puncture resistance of the positive electrode, reduces the risk of thermal runaway, and enhances the safety and ion transmission performance of large soft-pack batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637383A_ABST
    Figure CN120637383A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece of a large soft package battery cell, a preparation method of the positive pole piece, the large soft package battery cell and a plant protection unmanned aerial vehicle. The positive pole piece comprises an aluminum foil current collector and a positive pole material layer covering the surface of the aluminum foil current collector; a lithium manganese iron phosphate layer is also arranged between the positive electrode material layer and the aluminum foil current collector; and the positive electrode material layer comprises a lithium transition metal oxide positive electrode material, lithium manganese iron phosphate and an ion transmission reinforcing material. The positive pole piece comprises a lithium manganese iron phosphate layer and a positive pole material layer, and the LMFP layer is used as a physical barrier to isolate direct contact between an aluminum foil and a positive pole material, so that local temperature rise caused by puncture can be delayed, and the contact resistance is improved; the LMFP dispersed in the positive electrode material layer can block a thermal decomposition diffusion path, and the influence of the LMFP on the conductivity is counteracted by combining the high ionic conductivity of the ion transmission enhanced material; the laminated composite structure can absorb mechanical shock, inhibit energy release and block a thermal runaway chain reaction, so that the safety of the large soft package battery cell is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery cells, and relates to a positive electrode tab of a large soft-pack battery cell, and particularly to a positive electrode tab of a large soft-pack battery cell, a preparation method thereof, a large soft-pack battery cell and a plant protection UAV. Background Art

[0002] Plant protection UAVs are usually used for agricultural operations and greatly improve the efficiency of agricultural operations. At present, the power of plant protection UAVs generally adopts large soft-pack battery cells, and the positive electrode materials in the large soft-pack battery cells mainly adopt medium-high nickel ternary materials, and a small amount adopt lithium cobaltate materials. However, the large soft-pack battery cells prepared based on the existing positive electrode tabs have poor safety, and it is difficult to pass the severe针刺experiment. In actual use, if there is a slight impact, it will cause an internal short circuit, which may lead to thermal runaway, bringing potential personal danger to farmers' operations, and there is also a potential risk of forest fires or farmland damage caused by battery spontaneous combustion.

[0003] CN119447227A discloses a positive electrode active material, a positive electrode paste, a positive electrode tab, a battery and a vehicle, belonging to the technical field of batteries. The positive electrode active material includes lithium iron manganese phosphate and lithium nickel cobalt manganese oxide; wherein, the mass ratio of lithium iron manganese phosphate to lithium nickel cobalt manganese oxide is (50-95):(5-50); the chemical general formula of lithium nickel cobalt manganese oxide is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1. By compounding lithium iron manganese phosphate and lithium nickel cobalt manganese oxide as the positive electrode active material and controlling the mass ratio of the two within the range of (50-95):(5-50), when this positive electrode active material is applied to a battery, it can have high safety performance while having a relatively high energy density, improving the comprehensive performance. However, the puncture resistance of the positive electrode tab disclosed in this document still cannot meet the requirements in actual applications.

[0004] CN118943312A discloses a lithium ion battery positive electrode material, a positive electrode tab and a lithium ion battery. The lithium battery positive electrode material at least includes: a first positive electrode active material, and the first positive electrode active material includes any one or more of nickel cobalt manganese ternary material, lithium iron phosphate, lithium iron manganese phosphate, lithium-rich manganese-based material, lithium cobaltate or lithium nickel manganate; a second positive electrode active material, and the chemical general formula of the second positive electrode active material is Li x M 1-y N y O 4-z, where 0.05≤x≤6, 0≤y≤1, 0≤z≤2, the element M includes any one or more of Fe, Ni, or Co, and the element N includes any one or more of Al, Mn, Ti, Si, or Cu. Similarly, the puncture resistance of the positive electrode sheet disclosed in this document cannot meet the requirements of practical applications.

[0005] The positive electrode sheets disclosed in the prior art have poor puncture resistance, resulting in poor safety of large soft-pack batteries containing them. Therefore, it is crucial to develop and design a new positive electrode sheet for large soft-pack batteries, a preparation method thereof, a large soft-pack battery, and a plant protection drone. Summary of the Invention

[0006] In response to the deficiencies in the prior art, the present invention aims to provide a positive electrode sheet for a large soft-pack battery cell and a preparation method thereof, a large soft-pack battery cell and a plant protection drone. In the positive electrode sheet of the large soft-pack battery cell provided by the present invention, the positive electrode sheet provided by the present invention includes a lithium manganese iron phosphate (LMFP) layer and a positive electrode material layer containing LMFP and an ion transport enhancing material. The LMFP layer acts as a physical barrier to isolate the aluminum foil from direct contact with the positive electrode material. Its high thermal stability can delay the local temperature rise caused by puncture and suppress the risk of aluminum foil-negative electrode short circuit by increasing the contact resistance; the LMFP dispersed in the positive electrode material layer can block the thermal decomposition diffusion path, and combined with the high ionic conductivity of the ion transport enhancing material, it not only offsets the effect of LMFP on conductivity, but also synergistically stabilizes the electrode interface; the stacked composite structure (LMFP layer and positive electrode material layer) can absorb mechanical impact, inhibit energy release and block thermal runaway chain reaction, thereby optimizing the safety of the large soft-pack battery cell.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive electrode plate for a large soft-pack battery cell, the positive electrode plate comprising an aluminum foil current collector and a positive electrode material layer covering at least one side of the aluminum foil current collector;

[0009] A lithium manganese iron phosphate layer is further provided between the positive electrode material layer and the aluminum foil current collector;

[0010] The positive electrode material layer includes lithium transition metal oxide positive electrode material, lithium manganese iron phosphate and ion transport enhancing material.

[0011] In the positive electrode sheet of the large soft-pack battery cell provided by the present invention, a lithium iron manganese phosphate material layer (LMFP layer) is provided between the aluminum foil current collector and the positive electrode material layer. The lithium iron manganese phosphate material layer forms a physical isolation between the aluminum foil current collector and the positive electrode material layer, thereby improving the puncture resistance of the positive electrode sheet and reducing the risk of thermal runaway after puncture of the large soft-pack battery cell, thereby enhancing the safety of the large soft-pack battery cell; in addition, since the lithium iron manganese phosphate layer has high thermal stability, the lithium iron manganese phosphate layer can also eliminate the highest risk of aluminum foil-negative electrode material (aluminum exists in the aluminum foil current collector of the positive electrode sheet, and the negative electrode material exists in the negative electrode sheet) contact when the positive electrode sheet is short-circuited, and convert it into an internal short contact between the lithium iron manganese phosphate material and the negative electrode material, thereby improving the contact resistance, improving the puncture resistance of the positive electrode sheet, reducing the risk of thermal runaway of the large soft-pack battery cell, thereby enhancing the safety of the large soft-pack battery cell.

[0012] In the present invention, after the lithium manganese iron phosphate material is arranged in the positive electrode material layer, during the puncture test, if the lithium transition metal oxide positive electrode material in the positive electrode plate undergoes internal short-term thermal decomposition, the lithium manganese iron phosphate material uniformly dispersed in the lithium transition metal oxide positive electrode material can effectively block the further diffusion of the thermal decomposition, thereby reducing the risk of thermal runaway after the large soft-pack battery cell is punctured, thereby enhancing the safety of the large soft-pack battery cell.

[0013] In the present invention, by limiting the positive electrode material layer to also include ion transport enhancing material, the high ion conductivity of the ion transport enhancing material is utilized to improve the ion transport capacity of the positive electrode plate, reduce or offset the performance degradation of the positive electrode material layer caused by the incorporation of lithium manganese iron phosphate, thereby ensuring the ion transport performance of the positive electrode plate while reducing the risk of thermal runaway of the large soft-pack battery cell during the puncture process, thereby enhancing the safety of the large soft-pack battery cell.

[0014] In the positive electrode plate provided by the present invention, the lithium iron manganese phosphate layer acts as a physical barrier to prevent direct contact between the aluminum foil current collector and the positive electrode active material, and its high thermal stability can delay the local temperature rise during the puncture process; in addition, the lithium iron manganese phosphate dispersed in the positive electrode material layer can block the thermal decomposition diffusion path and inhibit the thermal runaway chain reaction, while the ion transport enhancing material compensates for the negative impact of lithium iron manganese phosphate on ion conduction and maintains high conductivity; in addition, the lithium iron manganese phosphate layer and the positive electrode material layer containing lithium iron manganese phosphate and ion transport enhancing material form a stacked composite structure, the lithium iron manganese phosphate layer absorbs mechanical impact and blocks direct contact between the aluminum foil and the negative electrode, the lithium iron manganese phosphate and the ion transport enhancing material in the positive electrode material layer cooperate to stabilize the interface, which not only reduces the risk of internal short circuit, but also improves the contact resistance and inhibits energy release, ultimately achieving the dual optimization of the structural integrity and safety of the large soft-pack battery cell.

[0015] Preferably, the thickness of the lithium manganese iron phosphate layer is 1 to 8 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In the present invention, when the thickness of the lithium iron manganese phosphate layer is 1 to 8 μm, the large soft-pack battery cell not only has a lower DC internal resistance and a higher discharge specific capacity, but also exhibits better performance in the puncture test. This is because the lithium iron manganese phosphate layer in this thickness range can balance the interface conductivity, ion transport performance and thermal management efficiency, and can ensure that the short-circuit current is fully dispersed through microcracks during puncture, and fully delay the direct contact between the aluminum foil and the graphite, thereby reducing the temperature rise rate. At the same time, it can also avoid mechanical protection failure and local hot spot diffusion caused by being too thin.

[0017] Preferably, the lithium manganese iron phosphate layer includes lithium manganese iron phosphate (LMFP), a conductive agent and a binder.

[0018] Preferably, the conductive agent in the lithium manganese iron phosphate layer includes any one or a combination of at least two of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene. Typical but non-limiting combinations include a combination of conductive carbon black and acetylene black, a combination of Ketjen black and carbon nanotubes, a combination of carbon nanotubes and graphene, or a combination of conductive carbon black, Ketjen black and graphene.

[0019] Preferably, the binder in the lithium manganese iron phosphate layer includes any one or a combination of at least two of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid or polyacrylonitrile. Typical but non-limiting combinations include a combination of polyvinylidene fluoride and sodium carboxymethyl cellulose, a combination of styrene-butadiene rubber and polyacrylic acid, a combination of polyacrylic acid and polyacrylonitrile, or a combination of polyvinylidene fluoride, styrene-butadiene rubber and polyacrylonitrile.

[0020] Preferably, based on the mass of the lithium iron manganese phosphate layer, the mass fraction of lithium iron manganese phosphate in the lithium iron manganese phosphate layer is 80-95wt%, the mass fraction of the conductive agent is 3-10wt%, and the mass fraction of the binder is 2-10wt%.

[0021] In the present invention, the mass fraction of the lithium iron manganese phosphate in the lithium iron manganese phosphate layer is 80-95wt%, for example, it can be 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92wt% or 95wt%, but is not limited to the listed values. Other values ​​not listed within each numerical range are also applicable.

[0022] In the present invention, the mass fraction of the conductive agent in the lithium manganese iron phosphate layer is 3 to 10 wt%, and the mass fraction can be 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%. However, it is not limited to the listed values, and other values ​​not listed within each numerical range are also applicable.

[0023] In the present invention, the mass fraction of the binder in the lithium manganese iron phosphate layer is 2 to 10 wt%, and can be, for example, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%, but is not limited to the listed values, and other values ​​not listed within each numerical range are also applicable.

[0024] In the present invention, the mass fraction of lithium manganese iron phosphate in the lithium manganese iron phosphate layer affects the performance of the positive electrode sheet and the large soft-pack battery cell; when the mass fraction of lithium manganese iron phosphate is 80-95wt%, the large soft-pack battery cell not only has a lower DC internal resistance and a higher discharge specific capacity, but also shows better performance in the needle penetration test. This is because when the mass fraction of lithium manganese iron phosphate is 80-95wt%, the lithium manganese iron phosphate layer has a higher content of lithium manganese iron phosphate, which is 3 + / Mn 4+ The redox pairs form a three-dimensional electron network, which reduces the interfacial contact impedance. During puncture, the high-risk Al-graphite contact can be avoided to a greater extent, and converted into an internal short contact between LMFP and graphite, thereby further reducing the risk of thermal runaway of the positive electrode.

[0025] Preferably, a carbon coating layer is further provided between the current collector and the lithium manganese iron phosphate layer.

[0026] Preferably, the thickness of the carbon coating layer is 0.3 to 1.0 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the carbon coating layer includes a conductive agent and a binder.

[0028] Preferably, the conductive agent in the carbon coating layer includes any one or a combination of at least two of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene. Typical but non-limiting combinations include a combination of conductive carbon black and Ketjen black, a combination of acetylene black and carbon nanotubes, a combination of carbon nanotubes and graphene, or a combination of acetylene black, Ketjen black and graphene.

[0029] Preferably, the binder in the carbon coating layer includes any one or a combination of at least two of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid or polyacrylonitrile. Typical but non-limiting combinations include a combination of polyvinylidene fluoride and styrene-butadiene rubber, a combination of sodium carboxymethyl cellulose and polyacrylic acid, a combination of polyacrylic acid and polyacrylonitrile, or a combination of polyvinylidene fluoride, sodium carboxymethyl cellulose and polyacrylonitrile.

[0030] Preferably, based on the mass of the carbon coating layer being 100%, the mass fraction of the conductive agent in the carbon coating layer is 50-90%, and the mass fraction of the binder is 10-50%.

[0031] In the present invention, the mass fraction of the conductive agent in the carbon coating layer is 50-90%, for example, it can be 50%, 60%, 70%, 80% or 90%, but it is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0032] In the present invention, the mass fraction of the carbon coating layer is 10% to 50%, and the mass fraction of the binder in the carbon coating layer is 10% to 50%, for example, it can be 10%, 20%, 30%, 40% or 50%, but it is not limited to the listed values. Other values ​​not listed within each numerical range are also applicable.

[0033] Preferably, based on the mass of the positive electrode material layer, the mass fraction of lithium manganese iron phosphate in the positive electrode material layer is 1-20 wt %, and the mass fraction of the ion transport enhancing material is 0.2-2 wt %.

[0034] In the present invention, the mass fraction of the positive electrode material layer is 1% to 20% by weight, and the mass fraction of lithium manganese iron phosphate in the positive electrode material layer is 1% to 20% by weight, for example, it can be 1% by weight, 3% by weight, 5% by weight, 7% by weight, 9% by weight, 11% by weight, 13% by weight, 15% by weight, 17% by weight, 19% by weight or 20% by weight, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] In the present invention, the mass fraction of the ion transport enhancing material is 0.2 to 2 wt%, based on the mass of the positive electrode material layer as a percentage, for example, it can be 0.2 wt%, 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt% or 2 wt%, but it is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0036] In the present invention, by limiting the mass fraction of lithium manganese iron phosphate and ion transport enhancing material in the positive electrode material layer, the thermal stability of the positive electrode material layer is further improved while ensuring the electrochemical performance of the positive electrode material layer, thereby reducing the risk of thermal runaway after puncture of the large soft-pack battery cell, thereby enhancing the safety of the large soft-pack battery cell.

[0037] Preferably, the ion transport enhancing material comprises any one or a combination of at least two of lithium aluminum titanium phosphate (LATP), lithium aluminate or lithium titanium phosphate. Typical but non-limiting combinations include a combination of lithium aluminum titanium phosphate and lithium aluminate, a combination of lithium aluminate and lithium titanium phosphate, a combination of lithium aluminum titanium phosphate and lithium titanium phosphate, or a combination of lithium aluminum titanium phosphate, lithium aluminate and lithium titanium phosphate.

[0038] Preferably, the lithium transition metal oxide positive electrode material includes any one or a combination of at least two of a ternary positive electrode material, a lithium cobaltate positive electrode material, a lithium manganate positive electrode material or a lithium nickelate positive electrode material. Typical but non-limiting combinations include a combination of a ternary positive electrode material and a lithium cobaltate positive electrode material, a combination of a lithium manganate positive electrode material and a lithium nickelate positive electrode material, a combination of a lithium cobaltate positive electrode material and a lithium manganate positive electrode material, a combination of a ternary positive electrode material and a lithium nickelate positive electrode material, or a combination of a ternary positive electrode material, a lithium cobaltate positive electrode material and a lithium manganate positive electrode material; preferably, a ternary positive electrode material or a lithium cobaltate positive electrode material.

[0039] Preferably, the chemical formula of the ternary cathode material is LiNi x Co γ MnzO2, x+y+z=1.

[0040] Preferably, the positive electrode material layer further includes a conductive agent and a binder.

[0041] Preferably, the conductive agent in the positive electrode material layer includes any one or a combination of at least two of graphite, conductive carbon black, acetylene black, carbon nanotubes or graphene. Typical but non-limiting combinations include a combination of graphite and conductive carbon black, a combination of acetylene black and carbon nanotubes, a combination of carbon nanotubes and graphene, a combination of conductive carbon black and graphene, a combination of graphite and acetylene black, or a combination of graphite, carbon nanotubes and graphene.

[0042] Preferably, the binder in the positive electrode material layer includes any one or a combination of at least two of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose or styrene-butadiene rubber. Typical but non-limiting combinations include a combination of polyvinylidene fluoride and polytetrafluoroethylene, a combination of sodium carboxymethyl cellulose and styrene-butadiene rubber, a combination of polytetrafluoroethylene and sodium carboxymethyl cellulose, a combination of polyvinylidene fluoride and styrene-butadiene rubber, a combination of polytetrafluoroethylene and styrene-butadiene rubber, or a combination of polyvinylidene fluoride, sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0043] Preferably, when the lithium transition metal oxide positive electrode material in the positive electrode material layer is a ternary positive electrode material, the mass ratio of the ternary positive electrode material, the conductive agent and the binder in the positive electrode material layer is (85-98):(1-8):(1-7).

[0044] When the lithium transition metal oxide positive electrode material in the positive electrode material layer of the present invention is a ternary positive electrode material, the mass ratio of the ternary positive electrode material to the conductive agent in the positive electrode material layer is (85-98):(1-8), for example, it can be 85:1, 88:2, 90:3, 92:4, 94:5, 96:6, 98:7 or 98:8, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0045] When the lithium transition metal oxide positive electrode material in the positive electrode material layer of the present invention is a ternary positive electrode material, the mass ratio of the ternary positive electrode material to the binder in the positive electrode material layer is (85-98):(1-7), for example, it can be 85:1, 88:2, 90:3, 92:4, 94:5, 96:6 or 98:7, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0046] Preferably, when the lithium transition metal oxide positive electrode material in the positive electrode material layer is lithium cobalt oxide, the mass ratio of lithium cobalt oxide, conductive agent and binder in the positive electrode material layer is (92-98):(1-4):(1-4).

[0047] When the lithium transition metal oxide positive electrode material in the positive electrode material layer of the present invention is lithium cobalt oxide, the mass ratio of lithium cobalt oxide to the conductive agent in the positive electrode material layer is (92-98):(1-4), for example, it can be 92:1, 94:2, 96:3 or 98:4, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0048] When the lithium transition metal oxide positive electrode material in the positive electrode material layer of the present invention is lithium cobalt oxide, the mass ratio of lithium cobalt oxide to binder in the positive electrode material layer is (92-98):(1-4), for example, it can be 92:1, 94:2, 96:3 or 98:4, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0049] Preferably, the thickness of the positive electrode material layer is 80 to 150 μm, for example, it can be 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm or 150 μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0050] Preferably, the positive electrode material layer has pit lines on the surface away from the aluminum foil current collector.

[0051] In the present invention, the pit lines can improve the electrolyte infiltration efficiency and promote Li+ diffusion by increasing the effective reaction area of ​​the active material, thereby reducing the DC internal resistance; at the same time, the mechanical stress buffer network formed by the pits can alleviate the volume expansion of the positive electrode particles during the charge and discharge cycle and inhibit crack propagation; in the needle penetration test, the pit structure can also disperse the local short-circuit current density, delay the direct contact between the aluminum foil and the negative electrode, and cooperate with the lines to guide the heat diffusion path, thereby improving the puncture resistance of the positive electrode sheet.

[0052] Preferably, the pit depth of the pit engraving line is 5 to 50 μm, and the width of the pit top is 30 to 200 μm.

[0053] The pit depth of the pit engraving line described in the present invention is 5 to 50 μm, for example, it can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0054] The width of the top of the pit of the pit engraving line described in the present invention is 30 to 200 μm, for example, it can be 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm or 200 μm, but is not limited to the listed values. Other unlisted values ​​within this numerical range are also applicable.

[0055] The width of the pit lines on the surface of the ternary positive electrode material layer in the present invention will affect the performance of the positive electrode plate and the large soft-pack battery cell; when the width of the pit lines is 30 to 200 μm, the large soft-pack battery cell not only has a lower DC internal resistance and a higher discharge specific capacity, but also exhibits better performance in the puncture test. This is because when the width of the pit lines is 30 to 200 μm, it can fully increase the contact area between the positive electrode material and the electrolyte, forming a low-impedance electron transmission path, and can also fully disperse the puncture stress, guiding the heat to diffuse laterally along the lines during puncture, thereby fully improving the puncture resistance of the positive electrode plate, and avoiding the decrease in mechanical strength of the positive electrode material layer caused by the excessive width of the pit lines, thereby ensuring the electrochemical performance of the positive electrode plate.

[0056] Preferably, both surfaces of the current collector are provided with a carbon coating layer, a lithium manganese iron phosphate layer and a ternary positive electrode material layer stacked in sequence.

[0057] In a second aspect, the present invention provides a method for preparing the positive electrode sheet according to the first aspect, the method comprising:

[0058] A lithium manganese iron phosphate layer and a positive electrode material layer comprising a lithium transition metal oxide positive electrode material, lithium manganese iron phosphate and an ion transport enhancing material are sequentially prepared on at least one side surface of an aluminum foil current collector to obtain the positive electrode sheet.

[0059] Preferably, before preparing the lithium manganese iron phosphate layer, the method further comprises: preparing a carbon coating layer on at least one side surface of the aluminum foil current collector.

[0060] Preferably, the method for preparing the carbon coating layer includes: dispersing the conductive agent and the binder in water to form a slurry, uniformly coating the slurry on the surface of the current collector by a spraying process, controlling the coating speed and slurry viscosity, and then drying and curing, and then rolling and heat treating to obtain the carbon coating layer.

[0061] Preferably, the method for preparing the lithium iron manganese phosphate layer includes: mixing lithium iron manganese phosphate, a binder, a conductive agent and a solvent to obtain a lithium iron manganese phosphate slurry, applying the obtained lithium iron manganese phosphate slurry to the surface of the carbon coating layer, and drying to obtain the lithium iron manganese phosphate layer.

[0062] Preferably, the solvent in the lithium manganese iron phosphate slurry includes any one or a combination of at least two of N-methylpyrrolidone, dimethylacetamide or water. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and dimethylacetamide, a combination of dimethylacetamide and water, a combination of N-methylpyrrolidone and water, or a combination of N-methylpyrrolidone, dimethylacetamide and water.

[0063] Preferably, the method for preparing the positive electrode material layer includes: mixing lithium transition metal oxide positive electrode material slurry, lithium iron manganese phosphate and ion transport enhancing material to obtain a positive electrode coating slurry, applying the obtained positive electrode coating slurry on the surface of the lithium iron manganese phosphate layer, and obtaining the positive electrode material layer after drying.

[0064] Preferably, the positive electrode material slurry includes any one of a ternary positive electrode material slurry, a lithium cobaltate slurry, a lithium manganate positive electrode material slurry or a lithium nickelate positive electrode material slurry, or a combination of at least two. Typical but non-limiting combinations include a combination of a ternary positive electrode material slurry and a lithium cobaltate slurry, a combination of a lithium manganate positive electrode material slurry and a lithium nickelate positive electrode material slurry, a combination of a lithium cobaltate slurry and a lithium manganate positive electrode material slurry, or a combination of a ternary positive electrode material slurry, a lithium cobaltate slurry and a lithium manganate positive electrode material slurry; preferably, it is a ternary positive electrode material slurry or a lithium cobaltate slurry.

[0065] Preferably, the ternary cathode material slurry includes a ternary cathode material, a conductive agent, a binder and a solvent.

[0066] Preferably, the solvent in the ternary positive electrode material slurry includes any one or a combination of at least two of N-methylpyrrolidone, dimethylacetamide or water. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and dimethylacetamide, a combination of dimethylacetamide and water, a combination of N-methylpyrrolidone and water, or a combination of N-methylpyrrolidone, dimethylacetamide and water.

[0067] Preferably, the method for preparing the ternary positive electrode material slurry comprises: mixing the ternary positive electrode material, a conductive agent, a binder and a solvent to obtain the ternary positive electrode material slurry.

[0068] Preferably, the lithium cobalt oxide slurry includes lithium cobalt oxide, a conductive agent, a binder and a solvent.

[0069] Preferably, the solvent in the lithium cobaltate slurry includes any one or a combination of at least two of N-methylpyrrolidone, dimethylacetamide or water. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and dimethylacetamide, a combination of dimethylacetamide and water, a combination of N-methylpyrrolidone and water, or a combination of N-methylpyrrolidone, dimethylacetamide and water.

[0070] Preferably, the method for preparing the lithium cobalt oxide slurry comprises: mixing lithium cobalt oxide, a conductive agent, a binder and a solvent to obtain the lithium cobalt oxide slurry.

[0071] Preferably, after preparing the positive electrode material layer, the method further comprises: laser scribing the surface of the obtained positive electrode material layer away from the aluminum foil current collector.

[0072] In a third aspect, the present invention provides a large soft-pack battery cell, which includes the positive electrode sheet described in the first aspect.

[0073] Typically, a large soft-pack battery cell consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the charge and discharge process, lithium ions are inserted and removed from the positive and negative electrodes. The separator is placed between the positive and negative electrodes to prevent short circuits and allow active ions to pass through. The electrolyte conducts active ions between the positive and negative electrodes.

[0074] The negative electrode in the present invention may optionally include a negative electrode current collector and a negative electrode film layer.

[0075] In the present invention, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0076] In the present invention, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present invention does not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0077] In the present invention, the negative electrode film layer may further optionally include a negative electrode binder. The present invention does not particularly limit the type of the negative electrode binder. For example, the negative electrode binder may include at least one of styrene-butadiene rubber, a water-soluble unsaturated resin, a water-based acrylic resin (e.g., polyacrylic acid, polymethacrylic acid, sodium polyacrylate), polyacrylamide, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan.

[0078] In the present invention, the negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0079] The negative electrode of the present invention does not exclude other additional functional layers in addition to the negative electrode film layer. For example, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. For example, the negative electrode of the present invention also includes a protective layer covering the surface of the negative electrode film layer.

[0080] In the large soft-pack battery cell of the present invention, there is no particular restriction on the type of separator used, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0081] In the present invention, the material of the separator can include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0082] In the present invention, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be made into a lithium-ion battery.

[0083] In the present invention, the outer packaging of the large soft-pack battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the large soft-pack battery cell can also be a soft package, such as a pouch-type soft package. The soft package can be made of plastic, such as at least one of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0084] In a fourth aspect, the present invention provides a plant protection drone, comprising the large soft-pack battery cell described in the third aspect.

[0085] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0086] Compared with the prior art, the present invention has the following beneficial effects:

[0087] (1) In the positive electrode sheet of the large soft-pack battery cell provided by the present invention, a lithium iron manganese phosphate material layer (LMFP layer) is provided between the aluminum foil current collector and the positive electrode material layer. The lithium iron manganese phosphate material layer forms a physical isolation between the aluminum foil current collector and the positive electrode material layer, thereby improving the puncture resistance of the positive electrode sheet and reducing the risk of thermal runaway after the large soft-pack battery cell is punctured, thereby enhancing the safety of the large soft-pack battery cell; in addition, since the lithium iron manganese phosphate layer has high thermal stability, the lithium iron manganese phosphate layer can also eliminate the highest risk of aluminum foil-negative electrode material (aluminum exists in the aluminum foil current collector of the positive electrode sheet, and the negative electrode material exists in the negative electrode sheet) contact when the positive electrode sheet is short-circuited, and convert it into an internal short contact between the lithium iron manganese phosphate material and the negative electrode material, thereby improving the contact resistance, improving the puncture resistance of the positive electrode sheet, reducing the risk of thermal runaway of the large soft-pack battery cell, thereby enhancing the safety of the large soft-pack battery cell;

[0088] (2) In the present invention, after the lithium iron manganese phosphate material is provided in the positive electrode material layer, during the puncture test, if the lithium transition metal oxide positive electrode material in the positive electrode plate undergoes internal short-term thermal decomposition, the lithium iron manganese phosphate material uniformly dispersed in the lithium transition metal oxide positive electrode material can effectively block the further diffusion of the thermal decomposition, thereby reducing the risk of thermal runaway after the large soft-pack battery cell is punctured;

[0089] (3) In the present invention, by limiting the positive electrode material layer to also include ion transport enhancing materials, the high ion conductivity of the ion transport enhancing materials is utilized to improve the ion transport capability of the positive electrode plate, thereby reducing or offsetting the performance degradation of the positive electrode material layer caused by the incorporation of lithium manganese iron phosphate, thereby ensuring the ion transport performance of the positive electrode plate while reducing the risk of thermal runaway of the large soft-pack battery cell during the puncture process. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 This is a flow chart of the method for preparing the positive electrode sheet of the large soft-pack battery cell in Example 1. DETAILED DESCRIPTION

[0091] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0092] Example 1

[0093] This embodiment provides a positive electrode plate for a large soft-pack battery cell, the positive electrode plate comprising a current collector (Al foil), and a ternary positive electrode material layer having a thickness of 100 μm and a carbon coating layer having a thickness of 0.6 μm, a lithium iron manganese phosphate layer having a thickness of 4.5 μm, and a ternary positive electrode material layer having a thickness of 100 μm, sequentially covering a surface of the current collector on one side; and a ternary positive electrode material layer having a thickness of 0.6 μm and a carbon coating layer having a thickness of 4.5 μm, and a ternary positive electrode material layer having a thickness of 100 μm, sequentially covering a surface of the current collector on the other side.

[0094] Based on the mass of the carbon coating layer, the carbon coating layer comprises 80% by mass of conductive carbon black and 20% by mass of polyvinylidene fluoride;

[0095] Based on the mass of the lithium iron manganese phosphate layer, the lithium iron manganese phosphate layer includes 90 wt % of lithium iron manganese phosphate, 6 wt % of conductive carbon black, and 4 wt % of polyvinylidene fluoride;

[0096] Based on the mass of the ternary positive electrode material layer, the mass fraction of lithium manganese iron phosphate in the ternary positive electrode material layer is 10wt%, and the mass fraction of lithium aluminum titanium phosphate is 1wt%;

[0097] The ternary positive electrode material layer further includes a ternary positive electrode material (chemical formula: LiNi 0.9 Co 0.6 Mn 0.4 O2), conductive carbon black and polyvinylidene fluoride;

[0098] The surface of the ternary positive electrode material layer away from the current collector has a pit line with a pit depth of 20 μm and a pit top width of 80 μm.

[0099] like Figure 1 As shown, the preparation method of the positive electrode sheet is:

[0100] (1) Conductive carbon black and polyvinylidene fluoride are dispersed in water to form a slurry, and the slurry is evenly coated on both sides of the current collector (Al foil) by a spraying process, while controlling the coating speed and slurry viscosity. After drying and curing, the slurry is rolled and heat-treated to obtain a carbon coating layer;

[0101] (2) mixing lithium iron manganese phosphate, polyvinylidene fluoride, conductive carbon black and water to obtain lithium iron manganese phosphate slurry, coating the obtained lithium iron manganese phosphate slurry on the surface of the carbon coating layer obtained in step (1), and drying to obtain a lithium iron manganese phosphate layer;

[0102] (3) mixing a ternary positive electrode material, conductive carbon black, polyvinylidene fluoride and water to obtain a ternary positive electrode material slurry; mixing the obtained ternary positive electrode material slurry, lithium iron manganese phosphate and lithium aluminum titanium phosphate to obtain a positive electrode coating slurry, coating the obtained positive electrode coating slurry on the surface of the lithium iron manganese phosphate layer obtained in step (2), and drying to obtain a ternary positive electrode material layer;

[0103] (4) Laser marking the surface of the ternary positive electrode material layer obtained in step (3) away from the current collector to obtain a positive electrode sheet.

[0104] Example 2

[0105] This embodiment provides a positive electrode plate for a large soft-pack battery cell, the positive electrode plate comprising a current collector (Al foil), and a ternary positive electrode material layer having a thickness of 0.3 μm, a thickness of 1 μm, and a thickness of 80 μm sequentially covered on one side of the current collector; and a ternary positive electrode material layer having a thickness of 0.3 μm, a thickness of 1 μm, and a thickness of 80 μm sequentially covered on the other side of the current collector.

[0106] Based on the mass of the carbon coating layer, the carbon coating layer comprises 90% by mass of acetylene black and 10% by mass of sodium carboxymethyl cellulose;

[0107] Based on the mass of the lithium iron manganese phosphate layer, the lithium iron manganese phosphate layer includes 95 wt % of lithium iron manganese phosphate, 3 wt % of graphene, and 2 wt % of styrene-butadiene rubber;

[0108] Based on the mass of the ternary positive electrode material layer, the mass fraction of lithium manganese iron phosphate in the ternary positive electrode material layer is 1wt%, and the mass fraction of lithium aluminum titanium phosphate is 0.2wt%;

[0109] The ternary positive electrode material layer further includes a ternary positive electrode material (chemical formula: LiNi 0.9 Co 0.6 Mn 0.4 O2), acetylene black and styrene-butadiene rubber;

[0110] The surface of the ternary positive electrode material layer away from the current collector has a pit line with a pit depth of 5 μm and a pit top width of 200 μm.

[0111] The preparation method of the positive electrode sheet is as follows:

[0112] (1) Acetylene black and sodium carboxymethyl cellulose are dispersed in water to form a slurry, and the slurry is evenly coated on both sides of the current collector (Al foil) by a spraying process, while controlling the coating speed and slurry viscosity. After drying and curing, the slurry is rolled and heat-treated to obtain a carbon coating layer;

[0113] (2) mixing lithium iron manganese phosphate, styrene-butadiene rubber, graphene and water to obtain lithium iron manganese phosphate slurry, coating the obtained lithium iron manganese phosphate slurry on the surface of the carbon coating layer obtained in step (1), and drying to obtain a lithium iron manganese phosphate layer;

[0114] (3) mixing a ternary positive electrode material, acetylene black, styrene-butadiene rubber and water to obtain a ternary positive electrode material slurry; mixing the obtained ternary positive electrode material slurry, lithium iron manganese phosphate and lithium aluminum titanium phosphate to obtain a positive electrode coating slurry, coating the obtained positive electrode coating slurry on the surface of the lithium iron manganese phosphate layer obtained in step (2), and drying to obtain a ternary positive electrode material layer;

[0115] (4) Laser marking the surface of the ternary positive electrode material layer obtained in step (3) away from the current collector to obtain a positive electrode sheet.

[0116] Example 3

[0117] This embodiment provides a positive electrode plate for a large soft-pack battery cell, the positive electrode plate comprising a current collector (Al foil), and a ternary positive electrode material layer having a thickness of 1.0 μm, a thickness of 8 μm, and a thickness of 150 μm sequentially covered on one side of the current collector; and a ternary positive electrode material layer having a thickness of 1.0 μm, a thickness of 8 μm, and a thickness of 150 μm sequentially covered on the other side of the current collector.

[0118] Based on the mass of the carbon coating layer, the carbon coating layer comprises 50% by mass of Ketjen black and 50% by mass of polyvinylidene fluoride;

[0119] Based on the mass of the lithium iron manganese phosphate layer, the lithium iron manganese phosphate layer includes 80 wt % of lithium iron manganese phosphate, 10 wt % of conductive carbon black, and 10 wt % of sodium carboxymethyl cellulose;

[0120] Based on the mass of the ternary positive electrode material layer, the mass fraction of lithium manganese iron phosphate in the ternary positive electrode material layer is 20wt%, and the mass fraction of lithium aluminum titanium phosphate is 2wt%;

[0121] The ternary positive electrode material layer further includes a ternary positive electrode material (chemical formula: LiNi 0.9 Co 0.6 Mn 0.4 O2), acetylene black and polyvinylidene fluoride;

[0122] The surface of the ternary positive electrode material layer away from the current collector has a pit line with a pit depth of 50 μm and a pit top width of 30 μm.

[0123] The preparation method of the positive electrode sheet is as follows:

[0124] (1) Ketjen black and polyvinylidene fluoride are dispersed in water to form a slurry, and the slurry is evenly coated on both sides of the current collector (Al foil) by a spraying process, while controlling the coating speed and slurry viscosity. After drying and curing, the slurry is rolled and heat-treated to obtain a carbon coating layer;

[0125] (2) mixing lithium iron manganese phosphate, sodium carboxymethyl cellulose, conductive carbon black and water to obtain lithium iron manganese phosphate slurry, coating the obtained lithium iron manganese phosphate slurry on the surface of the carbon coating layer obtained in step (1), and drying to obtain a lithium iron manganese phosphate layer;

[0126] (3) mixing a ternary positive electrode material, acetylene black, polyvinylidene fluoride and water to obtain a ternary positive electrode material slurry; mixing the obtained ternary positive electrode material slurry, lithium iron manganese phosphate and lithium aluminum titanium phosphate to obtain a positive electrode coating slurry, applying the obtained positive electrode coating slurry on the surface of the lithium iron manganese phosphate layer obtained in step (2), and drying to obtain a ternary positive electrode material layer;

[0127] (4) Laser marking the surface of the ternary positive electrode material layer obtained in step (3) away from the current collector to obtain a positive electrode sheet.

[0128] Example 4

[0129] This embodiment provides a positive electrode plate for a large soft-pack battery cell, which is the same as that of Example 1 except that the thickness of the lithium manganese iron phosphate layer is 0.5 μm.

[0130] Example 5

[0131] This embodiment provides a positive electrode sheet for a large soft-pack battery cell, which is the same as that of Example 1 except that the thickness of the lithium manganese iron phosphate layer is 12 μm.

[0132] Example 6

[0133] This embodiment provides a positive electrode plate for a large soft-pack battery cell. Except that the mass fraction of lithium iron manganese phosphate in the lithium iron manganese phosphate layer is 70wt%, the mass fraction of conductive carbon black is 15wt%, and the mass fraction of polyvinylidene fluoride is 15wt%, the rest are the same as in Example 1.

[0134] Example 7

[0135] This embodiment provides a positive electrode plate for a large soft-pack battery cell. Except that the mass fraction of lithium iron manganese phosphate in the lithium iron manganese phosphate layer is 98wt%, the mass fraction of conductive carbon black is 1wt%, and the mass fraction of polyvinylidene fluoride is 1wt%, the rest is the same as Example 1.

[0136] Example 8

[0137] This embodiment provides a positive electrode plate for a large soft-pack battery cell, which is the same as Example 1 except that the pit lines on the surface of the ternary positive electrode material layer are omitted, that is, step (4) in the preparation method of the positive electrode plate is omitted.

[0138] Comparative Example 1

[0139] This comparative example provides a positive electrode sheet for a large soft-pack battery cell, which is the same as Example 1 except that the lithium manganese iron phosphate layer is omitted.

[0140] Comparative Example 2

[0141] This comparative example provides a positive electrode sheet for a large soft-pack battery cell, which is the same as Example 1 except that the lithium manganese iron phosphate layer is disposed on the surface of the ternary positive electrode material layer away from the current collector.

[0142] Comparative Example 3

[0143] This comparative example provides a positive electrode sheet for a large soft-pack battery cell, which is the same as Example 1 except that the aluminum lithium titanium phosphate in the ternary positive electrode material layer is omitted.

[0144] Comparative Example 4

[0145] This comparative example provides a positive electrode sheet for a large soft-pack battery cell, which is the same as Example 1 except that lithium manganese iron phosphate and lithium aluminum titanium phosphate are omitted from the ternary positive electrode material layer.

[0146] Comparative Example 5

[0147] This comparative example provides a positive electrode plate for a large soft-pack battery cell, which is the same as Example 1 except that lithium manganese iron phosphate and lithium aluminum titanium phosphate in the ternary positive electrode material layer are omitted, and the carbon coating layer is omitted.

[0148] A large soft-pack battery cell is prepared using the positive electrode sheets provided in the above embodiments and comparative examples. The method for preparing the large soft-pack battery cell is as follows: the positive electrode sheets, graphite negative electrodes and polyethylene diaphragms provided in the above embodiments and comparative examples are stacked, and then hot-pressed at 80°C and a pressure of 1.2 MPa. After welding the tabs, the cells are vacuum-packaged with aluminum-plastic film. After injecting LiPF6 electrolyte, the cells are pre-charged (0.1C, 3.0-4.2V), formed (0.2C, 25°C) and aged (45°C, 24h) in sequence to obtain a large soft-pack battery cell.

[0149] The DC internal resistance of the large soft-pack battery cell was tested. The test method of the DC internal resistance is as follows: first adjust the battery cell to 50% SOC and let it stand for 30 minutes; then discharge it at a current of 0.1C, record the voltage OCV1 at the end of 10 seconds, and continue to discharge it to record the voltage OCV2 at the end of 11 seconds (acquisition accuracy 0.1s); calculate the internal resistance according to the formula DCR = (OCV1-OCV2) / 0.1C, where C is the rated capacity of the battery cell. The DC internal resistance of the large soft-pack battery cell is shown in Table 1.

[0150] The puncture performance of the large soft-pack battery cell was then tested. The test method for the puncture performance is as follows: the large soft-pack battery cell is charged to 100% SOC, and a 5mm diameter tungsten steel needle (cone angle 45°) is used to vertically pierce the thickest area of ​​the battery cell at 25±2°C. The puncture speed is 25mm / s. After penetration, the steel needle is kept for 1 hour to observe whether the large soft-pack battery cell catches fire or explodes within 1 hour. The observation results are as follows. The maximum temperature of the large soft-pack battery cell within 1 hour of the steel needle staying there is tested, and the test results are shown in Table 1.

[0151] The standard for large soft-pack batteries to pass the needle penetration test is that the large soft-pack batteries do not catch fire or explode within 1 hour of the steel needle staying there.

[0152] Table 1

[0153]

[0154] From Table 1, we can get:

[0155] (1) The large soft-pack battery cell prepared using the positive electrode sheets provided in Examples 1 to 3 of the present invention not only has a lower DC internal resistance and a higher discharge specific capacity, but also exhibits better performance in the needle penetration test and successfully passes the needle penetration test;

[0156] (2) By comparing Example 1 with Examples 4 and 5, it can be seen that the thickness of the lithium iron manganese phosphate layer in the present invention affects the performance of the positive electrode sheet and the large soft-pack battery cell; when the thickness of the lithium iron manganese phosphate layer is 1 to 8 μm, the large soft-pack battery cell not only has a lower DC internal resistance and a higher discharge specific capacity, but also shows better performance in the needle puncture test. This is because the lithium iron manganese phosphate layer in this thickness range can balance the interface conductivity, ion transport performance and thermal management efficiency, and can ensure that the short-circuit current is fully dispersed through microcracks during puncture, and fully delay the direct contact between the aluminum foil and the graphite, thereby reducing the temperature rise rate. At the same time, it can also avoid mechanical protection failure and local hot spot diffusion caused by being too thin;

[0157] (3) By comparing Example 1 with Examples 6 and 7, it can be seen that in the present invention, based on the mass of the lithium iron manganese phosphate layer as a percentage, the mass fraction of lithium iron manganese phosphate in the lithium iron manganese phosphate layer will affect the performance of the positive electrode sheet and the large soft-pack battery cell; when the mass fraction of lithium iron manganese phosphate is 80-95wt%, the large soft-pack battery cell not only has a lower DC internal resistance and a higher discharge specific capacity, but also shows better performance in the needle puncture test. This is because when the mass fraction of lithium iron manganese phosphate is 80-95wt%, the lithium iron manganese phosphate layer has a higher content of lithium iron manganese phosphate, which is obtained by Mn 3 + / Mn 4+ The redox pairs form a three-dimensional electron network, which reduces the interface contact impedance. During puncture, the high-risk Al-graphite contact can be avoided to a greater extent, and the internal short contact between LMFP and graphite can be converted, thereby further reducing the risk of thermal runaway of the positive electrode.

[0158] (4) By comparing Example 1 with Example 8, it can be seen that the pit lines on the surface of the ternary positive electrode material layer in the present invention will affect the performance of the positive electrode sheet and the large soft-pack battery cell; the pit lines can improve the electrolyte infiltration efficiency and promote Li+ diffusion by increasing the effective reaction area of ​​the active material, thereby reducing the DC internal resistance; at the same time, the mechanical stress buffer network formed by the pits can alleviate the volume expansion of the positive electrode particles during the charge and discharge cycle and inhibit crack propagation; in the needle puncture test, the pit structure can also disperse the local short-circuit current density, delay the direct contact between the aluminum foil and the negative electrode, and cooperate with the lines to guide the heat diffusion path, thereby improving the puncture resistance of the positive electrode sheet;

[0159] (5) By comparing Example 1 with Comparative Examples 1 to 5, it can be seen that in the positive electrode sheet of the large soft-pack battery cell provided by the present invention, a lithium iron manganese phosphate material layer is provided between the current collector and the positive electrode material layer. The lithium iron manganese phosphate material layer forms a physical isolation between the current collector and the positive electrode material layer, thereby improving the puncture resistance of the positive electrode sheet; in addition, since the lithium iron manganese phosphate material layer has high thermal stability, the lithium iron manganese phosphate material layer can also eliminate the possibility of the highest risk of Al-graphite contact when the positive electrode sheet is short-circuited, and convert it into an internal short contact between LMFP and graphite, thereby improving the contact resistance, thereby reducing the risk of thermal runaway of the positive electrode sheet and improving the puncture resistance of the positive electrode sheet;

[0160] In the present invention, after the lithium manganese iron phosphate material is provided in the positive electrode material layer, if the ternary positive electrode material or the lithium cobalt oxide positive electrode material undergoes internal short-term thermal decomposition, the lithium manganese iron phosphate material uniformly dispersed in the ternary positive electrode material or the lithium cobalt oxide positive electrode material can effectively block the further spread of the thermal decomposition, thereby reducing the risk of thermal runaway in large soft-pack batteries.

[0161] In the present invention, by limiting the positive electrode material layer to also include ion transport enhancing material, the high ion conductivity of the ion transport enhancing material is utilized to improve the ion transport capacity of the positive electrode plate, thereby reducing or offsetting the performance degradation of the positive electrode material layer caused by the incorporation of lithium manganese iron phosphate.

[0162] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode sheet for a large soft-pack battery cell, characterized in that: The positive electrode plate includes an aluminum foil current collector and a positive electrode material layer covering at least one side of the aluminum foil current collector; A lithium manganese iron phosphate layer is further provided between the positive electrode material layer and the aluminum foil current collector; The positive electrode material layer includes lithium transition metal oxide positive electrode material, lithium manganese iron phosphate and ion transport enhancing material.

2. The positive electrode sheet according to claim 1, characterized in that: The thickness of the lithium manganese iron phosphate layer is 1 to 8 μm; Preferably, based on the mass of the lithium iron manganese phosphate layer, the mass fraction of lithium iron manganese phosphate in the lithium iron manganese phosphate layer is 80-95wt%, the mass fraction of the conductive agent is 3-10wt%, and the mass fraction of the binder is 2-10wt%.

3. The positive electrode sheet according to claim 1, characterized in that: A carbon coating layer is further provided between the current collector and the lithium manganese iron phosphate layer; Preferably, the carbon coating layer has a thickness of 0.3 to 1.0 μm.

4. The positive electrode sheet according to claim 1, characterized in that: Based on the mass of the positive electrode material layer, the mass fraction of the lithium manganese iron phosphate in the positive electrode material layer is 1 to 20 wt%, and the mass fraction of the ion transport enhancing material is 0.2 to 2 wt%; Preferably, the lithium transition metal oxide positive electrode material includes any one of a ternary positive electrode material, a lithium cobalt oxide positive electrode material, a lithium manganese oxide positive electrode material or a lithium nickel oxide positive electrode material, or a combination of at least two thereof; preferably, a ternary positive electrode material or a lithium cobalt oxide positive electrode material; Preferably, the ion transport enhancing material comprises any one of lithium aluminum titanium phosphate, lithium aluminate or lithium titanium phosphate, or a combination of at least two thereof.

5. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material layer has pit lines on its surface away from the aluminum foil current collector; Preferably, the pit depth of the pit engraving line is 5 to 50 μm, and the width of the pit top is 30 to 200 μm; Preferably, both surfaces of the current collector are provided with a carbon coating layer, a lithium manganese iron phosphate layer and a ternary positive electrode material layer stacked in sequence.

6. A method for preparing the positive electrode sheet according to any one of claims 1 to 5, characterized in that: The preparation method comprises: A lithium manganese iron phosphate layer and a positive electrode material layer comprising a lithium transition metal oxide positive electrode material, lithium manganese iron phosphate and an ion transport enhancing material are sequentially prepared on at least one side surface of an aluminum foil current collector to obtain the positive electrode sheet.

7. The preparation method according to claim 6, characterized in that Before preparing the lithium manganese iron phosphate layer, the method further includes: preparing a carbon coating layer on at least one side surface of the aluminum foil current collector; Preferably, the method for preparing the lithium iron manganese phosphate layer comprises: mixing lithium iron manganese phosphate, a binder, a conductive agent and a solvent to obtain a lithium iron manganese phosphate slurry, applying the obtained lithium iron manganese phosphate slurry on the surface of the carbon coating layer, and drying to obtain the lithium iron manganese phosphate layer; Preferably, the method for preparing the positive electrode material layer includes: mixing lithium transition metal oxide positive electrode material slurry, lithium iron manganese phosphate and ion transport enhancing material to obtain a positive electrode coating slurry, applying the obtained positive electrode coating slurry on the surface of the lithium iron manganese phosphate layer, and obtaining the positive electrode material layer after drying.

8. The preparation method according to claim 6, characterized in that After preparing the positive electrode material layer, the method further comprises: performing laser scribing on the surface of the positive electrode material layer away from the aluminum foil current collector.

9. A large soft pack battery cell, characterized in that: The large soft-pack battery cell comprises the positive electrode sheet according to any one of claims 1 to 5.

10. A plant protection drone, characterized in that: The plant protection drone includes the large soft-pack battery cell according to claim 9.

Citation Information

Patent Citations

  • Positive electrode active material, positive electrode slurry, positive plate, battery and vehicle

    CN119447227A

Cited By

  • Positive pole piece of soft package battery cell, preparation method of positive pole piece and battery

    CN122246049A